The Relationship Between 3M Plus PSN Behavior and Physical Environmental Conditions with Dengue HF Incidents - Revi Meriska Wulandari; Nur Sefa Arief Hermawan; Dian Utami Pratiwi Putri (Universitas Ibn Khaldun Bogor, 2026)
Health concern in Indonesia, including Lampung Province. Data from the Lampung Provincial Health Office show a fluctuating trend: incidence declined from 50 per 100,000 population in 2022 to 23.4 in 2023, but sharply rose to 100 in 2024. In West Lampung Regency, the rate reached 208 per 100,000, well above the national target (≤ 49). At Fajar Bulan Public Health Center, incidence stood at 135 per 100,000 in 2024, with a case fatality rate (CFR) of 0%. These figures underscore the urgency of preventive efforts, particularly through “3M Plus” mosquito control and improved environmental sanitation. This study employed a quantitative case–control design conducted between June 28 and July 11, 2025, involving 120 respondents (60 cases and 60 controls) selected by total sampling. The independent variables were “3M Plus” practices and physical environmental conditions, while the dependent variable was DHF incidence. Data collection combined questionnaires and direct observation, analyzed using Chisquare with a significance level of 0.05. Findings indicated that most cases were associated with poor “3M Plus” practices and unsanitary environments, while the control group tended to have better conditions. Bivariate analysis revealed significant associations between both “3M Plus” behavior and DHF incidence (p < 0.05), as well as between environmental conditions and DHF incidence (p < 0.05). These results highlight the critical need to strengthen “3M Plus” practices and foster healthier environments as key strategies to reduce DHF risk in endemic areas.